ETIKA KERJA ISLAM SEBAGAI PENYEDERHANA DALAM HUBUNGAN ANTARA KECERDASAN EMOSI DAN KEPEMIMPINAN ADMINISTRATOR UNIVERSITAS NEGERI - Shukor, Abdul; bin Haji Abdul Ghani, Abdullah; bin Dato’ Abdul Rahman, Hamzah (Humanus, 2014)
The main challenges for the HEIs are to provide a market driven academic programmes and able to respond to the changing needs of economic sectors. Apparently, the recent challenges require the staff to equip themselves with leadership quality in order to achieve organizational goals. Previous studies have shown several factors such as EI influenced effective leadership. Another significant issue in leadership is ethical behaviors. Therefore, this study intends to examine the relationship between EI and leadership practices when Islamic work ethic is practiced in Malaysian public universities. The respondents will consist of middle administrators in Malaysian public universities. Using qualitative and cross sectional approaches, surveys will be distributed to the stratified randomly selected respondents. Most of the past results suggested there were significant relationships between the variables. The findings are expected to have some contributions both to the practical and theoretical aspects and enable PHIs to improve their leadership training programmes.Key words: Emotional intelligence, Islamic work ethic, and leadership